Risk Factors for Low Quality of Life among Women Using Different Types of Contraceptives in Saudi Arabia: A Questionnaire-Based Study - Malak M. Alhakeem; Leena R. Baghdadi; Almaha H. Alshathri; Aljohara H. Alshathri; Arwa A. Alqahtani; Monerah H. Alshathri (Behavioral Sciences, 2024)
This study aimed to assess and identify the risks for poor quality of life among female Saudi contraceptive users by administering an online questionnaire. The validity of the Arabic version of the Spanish Society of Contraception Quality of Life (SEC-QOL) questionnaire was assessed by incorporating the relevant items into an exploratory factor analysis and a subsequent confirmatory factor analysis. Internal consistency was assessed using Cronbach’s alpha coefficient. p < 0.05 was statistically significant. Questionnaires completed by 652 eligible women were analyzed. The most common contraception method was oral pills (51.5% of respondents). Analysis of the internal consistency of the questionnaire revealed that overall reliability was >0.7, which is considered adequate (Cronbach’s alpha = 0.845). Analysis of risk factors associated with higher overall SEC-QOL scores (worse overall quality of life) revealed several statistically significant variables. A “not good” relationship with their husbands, “heavy” menstrual flow, and premenstrual breast symptoms (breast pain, hypersensitivity, and increased size) were identified as risk factors for poor quality of life due to their association with the highest scores (poor quality of life). The Arabic version of the modified SEC-QOL is a valid and reliable tool to measure the quality of life of Saudi contraceptive users.